Perancangan Aplikasi Steganografi Berbasis Android dengan Metode Pixel Value Differencing (PVD) - Sinduningrum, Estu; Supriyanto, Anton (MULTINETICS, 2016)
Simplicity in message exchanges on current technological developments. But on the other hand it brings new problems in terms of security of the message. One method used to overcome this problem is steganography. Steganography is a technique for hiding information on an image. The purpose of this study is to analyze the quality of the images used steganography to hide text messages. One of steganography techniques to be used in this research is Pixel Value Differencing (PVD).  Quality of the image of will be declined. The application will be tested using .bmp, .png and .jpg images types and quality of steganography image is tested by calculating the Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR) results of the insertion process of the message. The results of the study showed that the characteristics of the image greatly affect the capacity of the message and the quality of the image after embedded message. Images with different sizes and types tested using MSE get values between 1.62022 dB and 0.000116 dB and using PSNR get values between 46.0 dB and 90.0 dB. This shows that the qualities between the original images and the steganography images are not much different. It can be concluded that the quality of the image are slightly different